High-resolution within-sewer SARS-CoV-2 surveillance facilitates informed intervention. (1st October 2021) - Reeves, Katelyn; Liebig, Jennifer; Feula, Antonio; Saldi, Tassa; Lasda, Erika; Johnson, William; Lilienfeld, Jacob; Maggi, Juniper; Pulley, Kevin; Wilkerson, Paul J.; Real, Breanna; Zak, Gordon; et al.
Highlights: Daily medical individual data compared to wastewater SARS-CoV-2 concentrations. Design, detail, and implementation of a low-cost composite autosampler. Comparison of two RT-qPCR detection approaches. Abstract: To assist in the COVID-19 public health guidance on a college campus, daily composite wastewater samples were withdrawn at 20 manhole locations across the University of Colorado Boulder campus. Low-cost autosamplers were fabricated in-house to enable an economical approach to this distributed study. These sample stations operated from August 25th until November 23rd during the fall 2020 semester, with 1512 samples collected. The concentration of SARS-CoV-2 in each sample was quantified through two comparative reverse transcription quantitative polymerase chain reactions (RT-qPCRs). These methods were distinct in the utilization of technical replicates and normalization to an endogenous control. (1) Higher temporal resolution compensates for supply chain or other constraints that prevent technical or biological replicates. (2) The data normalized by an endogenous control agreed with the raw concentration data, minimizing the utility of normalization. The raw wastewater concentration values reflected SARS-CoV-2 prevalence on campus as detected by clinical services. Overall, combining the low-cost composite sampler with a method that quantifies the SARS-CoV-2 signal within six hours enabled actionable and time-responsive data delivered to key stakeholders. With daily reporting of the findings, wastewater surveillance assisted in decision making during critical phases of the pandemic on campus, from detecting individual cases within populations ranging from 109 to 2048 individuals to monitoring the success of on-campus interventions. Graphical abstract: Tracking SARS-CoV-2 in on-campus wastewater informs and monitors public health decisions and actions. Image, graphical abstract